BUSPERAK: Menilik Kebaharuan Kurikulum Merdeka Melalui Pengembangan Bahan Ajar - Alfian Nur Muzaki; Tuti Mutia (Universitas Negeri Gorontalo, 2023)
The independent curriculum emphasizes literacy skills, including critical thinking and communicative skills as outlined in the teaching materials. The advantages of busperak teaching materials are QR codes, internet searches, and reinforcement of material for each chapter. The aim of this research is alternative high school level textbooks for grade XI because there are still few textbooks that adopt the independent curriculum. Research and development using ADDIE models the reseach methodology to produce busperak. The research instrument used validity sheets and questionnaires. The method of data analysis applies a descriptive percentage. Descriptive percentage technique is the process of converting quantitative data into qualitative data by analyzing the level of validity Implications showed that the media validity results scored 4.6, the material validity test scored 4.8 and the language validity test scored 4.6. Thus, the results of busperak validation obtained a validity level of 90% having an excellent category. Even while the small groups find trial show a percentage of 82% in media test, the material validity test gets a percentage of 79%, and the language validity test gets a percentage of 74%. So, total average result of the busperak product trial has a percentage of 78.333%. Thus, the busperak is categorized as good and suitable and can be applied at school.